Analisis Pengaruh Perilaku Konsumen terhadap Proses Keputusan Pembelian Produk Sliced Beef Secara Online Melalui Platform E-Commerce - Akbar Riza Ananda; Siti Azizah (Politeknik Baubau, 2023)
This research was conducted to determine the factors of consumer behavior that can influence the beef purchasing decision process through e-commerce. In this study, data collection was carried out using a questionnaire. The questionnaire used in this study was a closed questionnaire with a Likert scale using Google Forms media. The sampling technique was carried out by random sampling, the conditions for the respondents used in this study were those who had purchased beef products through e-commerce. The number of samples in this study were 100 respondents. The results of this study indicate that the factors of consumer behavior which include personal factors, psychological factors, cultural factors, and social factors together have a significant influence on the buying decision process. This is due to consumers' curiosity about beef products and the ease of shopping online. This consumer behavior can be used as a measuring tool to predict purchasing decisions. Cultural factors partially have no significant effect on the decision to purchase beef products through e-commerce platforms as evidenced by the partial test results.